"Western imitation" in modern China's urban planning practice between the Late Qing Dynasty and the Early Republic of China (1860-1927) - Ren, Xiaogeng; Li, Baihao; Shi, Diwen (International Planning History Society Proceedings, 2018)
At the Late Qing Dynasty and the Early Republic of China, the ancient Chinese city was gradually transformed into a form that closes to a city with modern significance in terms of nature, the concept of construction, the management system and the spatial structure. Since the Western powers had previously dominated the global capital trade model and implemented the urban planning and construction paradigm, most of the modern Chinese learned and imitated the western models when they re-planned the original Chinese city areas. From the main source of imitation, it contains three categories: the concession, Japan, Europe and the United States. From the practitioner of imitation, most of them are politicians, social reformers, intellectuals with western culture and overseas Chinese with advanced notions. Their understanding and longing for the western urban planning laid the foundation of the transformation of China's modern urban planning. Based on relevant historical materials and existing researching literature, this paper analyses the process of understanding, imitating and implementing in modern China’s urban planning practice between 1860-1927 so as to make it clear that the particularity and universality in the birth and formation of modern Chinese urban planning.